An Analytical Study of the Relationship Between Gross National Happiness (GNH) of Bhutan and Buddhist Peaceful Means - Gyemo, Kinley; Phramaha Weerasak Abhinandavedi; Ugyen Tshering (The Journal of International Buddhist Studies College, 2025)
This study investigates the relationship between Gross National Happiness (GNH) of Bhutan and Buddhist Peaceful Means through a documentary analysis approach. The research focuses on three objectives: (1) the concepts and theories of GNH, (2) the role of Buddhist Peaceful Means in fostering happiness, and (3) the interconnection between GNH and Buddhist principles. Data were collected from primary Buddhist scriptures, Bhutanese policy documents, and scholarly literature, and analyzed using descriptive statistics and content analysis. Key findings: GNH concept and theory. GNH frames development around four pillars: good governance, sustainable socio-economic development, cultural preservation, and environmental conservation, and uses nine domains to measure multidimensional well-being; the 2008 democratic transition institutionalized these principles in state policy. Buddhist peaceful means. Core practices, ethical conduct, mindfulness, loving-kindness (mettā), and bodhicitta, address the Three Poisons (desire, hatred, ignorance) and foster individual and communal well-being. Interconnection. GNH and Buddhist peaceful means are mutually reinforcing: policy instruments reflect Buddhist ethical priorities, while contemplative ethics support the social conditions necessary for GNH outcomes. The study concludes that Bhutan’s model exemplifies a reciprocal integration of institutional design and moral formation, suggesting that durable national well-being depends on coordinated policy instruments alongside programs that cultivate ethical and contemplative capacities. Future research should employ mixed methods and field-based inquiry to assess causal pathways from spiritual practice to measurable well-being outcomes.